Analisis User Experience pada Aplikasi E-Office Sumedang Menggunakan Metode User Experience Questionnaire (UEQ) Studi Kasus: Kantor Kecamatan Rancakalong - Inne Natya; Dwi Yuniarto; David Setiadi (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The purpose of this study is to analyze the use of the Sumedang E-Office application in order to improve service quality using the User Experience Questionnaire (UEQ) [1]. This study uses the User Experience Questionnaire (UEQ) survey methodology, and this study also collects survey data and a sample size of 25 people. The data sources for this study are primary data and secondary data. The research stage begins by determining the formulation of the problem, analyzing needs, defining questions, identifying respondents, measuring UEQ, and finally drawing conclusions. The results of this study indicate that the quality of the Sumedang E-Office application service still needs to be improved. This is supported by the results of the benchmark graph which is on average in the red range, namely the bad range. Of the six dimensions or existing measurements, those that need to be updated or improved: attractiveness, accuracy, stimulation and novelty.